2018
DOI: 10.1098/rspb.2018.1935
|View full text |Cite
|
Sign up to set email alerts
|

Computational biomechanical analyses demonstrate similar shell-crushing abilities in modern and ancient arthropods

Abstract: The biology of the American horseshoe crab, Limulus polyphemus, is well documented-including its dietary habits, particularly the ability to crush shell with gnathobasic walking appendages-but virtually nothing is known about the feeding biomechanics of this iconic arthropod. Limulus polyphemus is also considered the archetypal functional analogue of various extinct groups with serial gnathobasic appendages, including eurypterids, trilobites and other early arthropods, especially Sidneyia inexpectans from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 63 publications
2
68
0
Order By: Relevance
“…R. Soc. B 286: 20192371 spines (figure 2) resemble those of extant arthropods such as horseshoe crabs, implying the capabilities of tearing hard food items, and therefore predatory and/or scavenging behaviour [20]. This supports the conclusion drawn from comparison of the digestive system of N. spinosa with Recent arthropods [17].…”
Section: Discussionsupporting
confidence: 62%
“…R. Soc. B 286: 20192371 spines (figure 2) resemble those of extant arthropods such as horseshoe crabs, implying the capabilities of tearing hard food items, and therefore predatory and/or scavenging behaviour [20]. This supports the conclusion drawn from comparison of the digestive system of N. spinosa with Recent arthropods [17].…”
Section: Discussionsupporting
confidence: 62%
“…Cambrian-aged trilobites and other artiopodans that display gnathobases on protopodal sections of thoracic appendages were potentially durophagous predators that fed like horseshoe crabs (Babcock, 2003;Bicknell et al, 2018a;Bicknell et al, 2018b;Bicknell et al, 2018c;Bicknell, Pates & Botton, 2018d;Bicknell & Paterson, 2018;Holmes, Paterson & García-Bellido, in press). An example of this is Sidneyia inexpectans Walcott, 1911 that is known to have shelly cololites (Bruton, 1981;Zacaï, Vannier & Lerosey-Aubril, 2016;Peel, 2017;Bicknell & Paterson, 2018) and fortified gnathobasic spines for effective durophagy (Bicknell et al, 2018c).…”
Section: Potential Predatorsmentioning
confidence: 99%
“…Repaired injuries on Cambrian trilobite exoskeletons are well known (see Owen 1985;Babcock 1993Babcock , 2003Vinn 2018; Paterson 2018 for reviews) and trilobite rich gut contents (Conway Morris 1977;Bruton 1981;Zhu et al 2004;Vannier 2012;Zacaï et al 2016;Jago et al 2016) and coprolites (Sprinkle 1973; Conway Morris and Robison 1988;Nedin 1999;Babcock 2003, Skinner 2005Vannier and Chen 2005;English and Babcock 2010;Daley et al 2013;Kimmig and Strotz 2017) confirm that trilobites were prey items. Additionally, recent biomechanical analyses that built on functional morphological studies have confirmed that at least some Cambrian predators, such as Sidneyia inexpectans of the middle Cambrian Burgess Shale, were mechanically capable of injuring trilobites (Bicknell et al 2018a, b). Trilobites likely engaged in anti-predatory behaviors, such as burrowing, hiding, and enrolment (Fortey 1986;Esteve et al 2011Esteve et al , 2013Fatka and Budil 2014), and had select exoskeletal characters with anti-predatory roles: elongate spines and thick biomineralised exoskeletons (Fortey and Owens 1999;Clarkson and Ahlberg 2002).…”
Section: Trilobites As a Study Systemmentioning
confidence: 99%